Creative Marketing Strategies for Food SMEs: Enhancing Brand Visibility and Customer Loyalty in a Competitive Market and Economy - Novie, Muhafidhah (International Journal of Economics Development Research (IJEDR), 2024)
This study explores the effectiveness of creative marketing strategies for food SMEs in enhancing brand visibility and customer loyalty within competitive markets, specifically focusing on SMEs in East Java, Indonesia. Given the resource constraints typically faced by SMEs, creative marketing approaches such as storytelling, local collaborations, and social media engagement offer cost-effective means of differentiating brands and establishing strong customer connections. Using a qualitative approach, data were collected through in-depth interviews, observations, and document analysis, focusing on the perspectives and experiences of food SME owners and managers. Findings reveal that personalized customer interactions, community-centered branding, and digital engagement play a critical role in building both brand visibility and loyalty. Additionally, the study identifies key internal and external factors influencing the success of these marketing strategies, including resource limitations, customer preferences, and market competition. Practical implications suggest that food SMEs can enhance their market presence by focusing on authentic and customer-centric marketing tactics, while theoretical contributions highlight the need for adaptive, innovative approaches in creative marketing for SMEs. This study further proposes future research directions, including quantitative analyses and cross-cultural comparisons, to deepen the understanding of creative marketing impacts on SME sustainability and growth.